Magnetic Nanoparticle-Based Ligand Replacement Strategy for Chemical Luminescence Determination of Cholesterol - Wu, Yalan; Peng, Danfeng; Qi, Zhiwen; Zhao, Jing; Huang, Wenyi; Zhang, Ying; Liu, Changhui; Deng, Tao; Liu, Fang (Frontiers in Chemistry, 2020)
Determination of serum cholesterol (Chol) is important for disease diagnosis, which has attracted great efforts during the last few decades. Herein, a new magnetic nanoparticle-based ligand replacement strategy has been presented for chemical luminescence detection of Chol. The detection is based on the competitive interaction between Chol and ferrocene in binding to β-cyclodextrin (β-CD) through host-guest interaction, which releases Fc-Hemin as a catalyst for luminol/H2O2 chemical luminescence system. More importantly, the luminescence signal can be captured by the camera of a smartphone, thus realizing Chol detection with less instrument dependency. The limit of detection (LOD) of this method is calculated to be 0.18 μM, which is comparable to some of the developed methods. Moreover, this method has been used successfully to quantify Chol from serum samples with a simple extraction process.